Análise de SSCP de isolados do citrus tristeza virus e sua sintomatologia em clones de laranja pêra em três regiões do Estado de São Paulo - Temporal, Walter Magri (2009)
The Citrus tristeza virus (CTV) presents a vast biological diversity and it may cause different symptoms according to its interaction with the host plant and due to environmental conditions, especially temperature. The present study aims to evaluate the performance of different combinations of sweet orange cultivars and strains of CTV in experimental fields located in the northern, central and southern regions of São Paulo state. The combinations were evaluated through the analysis of symptomatology, crops, biological indexing and the SSCP analysis of the virus capsid protein gene. The treatments consisted of clones of four cultivars, Pêra IAC, Pêra IAC 2000, Pêra Olímpia and Ipiguá, original ones and shoot tip grafteds that were pre-immunized with the PIAC complex. The data referring to symptomatology, crops and biological testing revealed that the plants belonging to fields located both in the northwestern and central regions of the state, where averages of temperature were higher, seemed to be more resistant to the tristeza than the plants located in the southern fields, what suggests a correlation between severe symptoms of tristeza and lower temperatures. The SSCP analysis revealed that, in spite of the change in the original profile, the protective capacity of the weak virus used in the pre-immunization was maintained in the fields from the cities of Cajobi and Cordeirópolis, located in the northwestern and central regions of the state. In addition to that, the majority of the plants presented a profile that was similar to the PIAC.